ANALISIS PENGARUH JUMLAH WAJIB PAJAK TERHADAP PENERIMAAN PPH BADAN PADA KPP PRATAMA TELANAIPURA - Johandri Iqbal; Pramesti Nurul Adinda; Lady Matari Nainggolan (LP2M Politeknik Jambi, 2025)
This study aims to analyze the effect of the Number of Taxpayers on Corporate Income Tax Revenue at KPP Pratama Telanaipura Jambi during the 2019-2023 period. Using a quantitative approach with simple linear regression analysis method, this research processes secondary data from KPP Pratama Telanaipura Jambi's annual reports. The analysis results show that the Number of Taxpayers has no significant effect on Corporate Income Tax Revenue, with a significance value of 0.075 (>0.05) and determination coefficient of 0.706. These findings imply that increasing tax revenue requires a comprehensive approach that focuses not only on expanding the taxpayer base but also on improving compliance and tax administration effectiveness.